Development of exchange and over-the-counter derivatives of financial instruments in Russia - Ali Haitham Eid (Вестник университета)
Since there is an active trend of increasing derivative instruments in the Russian derivatives market, the object of this study was exchange-traded and over-the-counter derivatives in Russia, and the purpose of the study – the development of their application. To achieve this goal, such scientific research methods as analysis, comparison, description and historical method are used. The most important conclusions of the study are that the derivatives market has developed rapidly since 2013, but in 2021 it witnessed a significant increase due to the appeal of a large number of investors to invest in financial markets, and due to increased concern about the volatility of the exchange rate, due to which many dealers dealing in derivatives buy these instruments sometimes for the purpose of hedging, and at other times for the purpose of speculation or both.